FAKTOR-FAKTOR YANG MEMENGARUHI PENDAPATAN NELAYAN PANCING DI DESA KOLO BAWAH KECAMATANMAMOSALATO KABUPATEN MOROWALI UTARA - Ulfa Ulfa; Alimudin Laapo; Muh Fahruddin Nurdin (Universitas Tadulako, 2022)
This study aims to determine the effect of production costs, fishing experience, fishing distance, and fish prices on the income of fishing rods in Kolo Bawah Village, Mamosalato Subdistrict, North Morowali Regency. This research was conducted from June to July 2021. The determination of respondents in this study was carried out using a random sample method, with a total sample of 44 respondents from a total population of 270 people. The analysis used is multiple linear regression analysis. The results of the analysis show that the variable cost of production is 0.059, experience at sea is 31.039, the distance to sea is 13.710, and the price of fish is 10.540, has a real and significant effect both partially and simultaneously on the income of fishing fishermen in Kolo Bawah Village, Mamosalato District, North Morowali Regency.